Self-excited small scale hydropower generator in Malaysia: a brief review - Khairul Azhar bin Mat Daud; Nik Fazli Sapian; Ahmad Rasdan Ismail; Wan Azlina Wan Ismail (2014)
Houses and small farms in remote area typically use batteries or generator for their lighting and electricity needs. However, with the use of generators, the availability and cost of fuel to power the generators are of the main concerns. Other type of renewable energy such as wind and solar, which is only available for several hours per day; are also very costly. Hence, a cheaper and reliable option is needed. Although large hydropower plant provides electricity for industry and domestic use, small scale hydropower plant does contributes toward providing this basic need to remote, off-grid areas and backup power particularly in developing countries. Thus, this paper focuses on small scale hydropower, self-excited application which does not require river-run-off or dam for water storage. It is cost effective, environmentally friendly and the turbine system can be manufactured locally. Several existing research in Malaysia are highlighted and small scale hydropower is reviewed based on their application on rural environment.